INDIAN CULTURE (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article delves into the multifaceted aspects of Indian culture, exploring its diversity, traditions, and the impact of globalization. Through a comprehensive literature analysis, we examine the rich tapestry of Indian cultural elements, followed by a discussion on methods employed for cultural preservation. The results section highlights the resilience and evolution of Indian culture in the face of modern influences. The discussion section explores the implications of cultural dynamics on society, and the conclusion provides insights and suggestions for the preservation and appreciation of this intricate heritage.